KEJELASAN SASARAN ANGGARAN DAN SISTIM PENGENDALIAN AKUNTANSI TERHADAP KINERJA MANAJERIAL DENGAN MOTIVASI SEBAGAI VARIABEL MODERATING - Paulus Peka Hayon (EKONOMI & SOSIAL, 2016)
The aims of the research are to investigate and analyze 1) the effect of  the clarity budget goal on the managerial performance of local government, 2) the effect of accounting control system on the managerial performance of local government, 3) the simultaneous effect of the clarity of budget goal, accounting control system, and work motivation on managerial performance, 4) the effect of motivation as the moderating variable that makes the correlation between the clarity of budget goal and accounting control system strong on the managerial performance of local government.  The population of the research were the officials who were budget providers   and users and responsible for accounting control system. The sample consisted of 102 people and the data were analyzed using moderating regression analysis.  The results of the research indicate that  1) the clarity of budget goal  has effect on the managerial performance of local government, 2) accounting control system has affect on the managerial performance of local government, 3) the clarity of budget goal, accounting control system, and work motivation simultaneously have affect on the managerial performance of local government, 4) work motivation can become moderating variable affecting the clarity of budget goal on the managerial performance of local government. Work motivation can not become effect moderating variable of accounting control system on the managerial performance of local government (an empirical study at SKPD  of Merauke Regency).